Analysis of law enforcement against illegal rare earth sales in bangka district - Hanaya, Esther; Maulana, Izza; Safitri, Anggi (Journal of Law Science, 2024)
Mining in Indonesia is a promising sector, including the management of rare earths, which are mining residues with high selling value. In Bangka Belitung, rare earths mainly come from tin mining residues. Although Government Regulation No. 96 of 2021 has recognized rare earths as one of the five categories of mineral and coal mining that must be managed with a Mining Business License (IUP), specific regulations regarding rare earths have not been discussed in detail. As a result of these regulatory limitations, many entrepreneurs take advantage of legal loopholes to sell rare earths illegally, both inter-city and export. This research aims to examine the specific regulations governing rare earths and uncover the reasons why illegal sellers are reluctant to officially register their companies, particularly in Bangka Belitung. This research uses an empirical juridical method that focuses on applicable laws and regulations to uncover problems in the field, by adhering to normative provisions related to illegal rare earth sales in the Bangka Belitung Islands. Researchers found that several regulations related to rare earths include Law Number 3 of 2020 concerning Mineral and Coal Mining (Minerba Law), Government Regulation Number 23 of 2010 concerning the Implementation of Mineral and Coal Mining Business Activities, Government Regulation No. 96 of 2021, and MEMR Regulation No. 25 of 2018 which has been updated to Minister of Energy and Mineral Resources Decree Number 301. K/MB.01/MEM.B/2022, which regulates the National Plan for Mineral and Coal Mining for 2022-2027